School eye survey in rural population in UP, India - Gupta, Y; Sukul, RR; Gupta, M; Phougat, A; Jain, R; Varshney, A (Nepalese Journal of Ophthalmology, 2011)
Objective: To find out the prevalence of refractive errors and pattern of ocular morbidity amongst the school children of a rural village. Materials and methods: A cross sectional study was carried out in children of age group 3 – 12 years in a rural village of Hathras, Uttar Pradesh, India. All the children were examined including visual acuity measurement using Snellen’s E chart, retinoscopy and refraction under cycloplegia. Examination of the anterior segment, media, and fundii was also done. Myopia was defined as spherical/cylindrical equivalent refractive error of at least -0.50 D and hypermetropia as +0.50 D or more (Dandona et al 2002). Results: In the survey 220 eyes of 110 children were examined, majority of them were in 5-10 year age group. The prevalence of uncorrected visual acuity of 6/6 was 85.40%. Refractive error was the cause in 6.81% of eyes with vision impairment, out of which myopia and hypermetropia were present in 26.67% of eyes. Blepharo-conjunctivitis was present in 15.45% of children and Bitot’s spots were present in 0.90% of them. Colour blindness was found in one child. Conclusion: The prevalence of refractive error in rural school is 6.81 %. Blepharitis is the commonest cause of ocular morbidity. DOI: 10.3126/nepjoph.v3i1.4282 Nepal J Ophthalmol 2011;3(5):78-79